Low-level inhibition of Hsp90 forces cells to tip their (antigenic) hand - Srivastava, Pramod K. (Clin Cancer Res, 2019)
Low-level inhibition of hsp90 enhances the antigenicity of cells whereas high-level inhibition diminishes antigenicity. The mechanism(s) by which hsp90 determines antigenicity are only partially clear. Regardless, these observations have profound implications in protein trafficking and antigen presentation and suggest a novel way to enhance the potency of existing anti-cancer agents.